Public control influence during elections campains on democratization state power in Ukraine - Логачова, В. В. (Theory and practice of jurisprudence, 2016)
This article is devoted to the problems of the public control realization on the elections. Taking as an example the pre-election campaign, the significance of the public control on the election in Ukraine have been determined in the article and different possible ways of such a control efficiency increasing in practice taking into account the foreign states experience have been proposed